2020
DOI: 10.3389/fpsyt.2020.576214
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Δ9-Tetrahydrocannabinol Exposure Selectively Impairs Working Memory but Not Several Other mPFC-Mediated Behaviors

Abstract: As the frequency of cannabis use by 14–16-year-olds increases, it becomes increasingly important to understand the effect of cannabis on the developing central nervous system. Using mice as a model system, we treated adolescent (28 day old) C57BL6/J mice of both sexes for 3 weeks with 3 mg/kg tetrahydrocannabinol (THC). Starting a week after the last treatment, several cognitive behaviors were analyzed. Mice treated with THC as adolescents acquired proficiency in a working memory task more slowly than vehicle-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
(72 reference statements)
2
4
0
Order By: Relevance
“…Further, we showed that impairment of the ghrelin signaling through the knockout of the GHRS does not confer an increased risk of developing THC induced anxiety in adult mice. Our results are consistent with previous reports in rodent models that concluded that prolonged adolescent THC exposure in mice does not have substantive negative impacts on several mPFC-mediated behaviors [47][48][49][50]. In particular, Chen et al [49] treated 28-day-old C57BL6/J mice of both sexes for three weeks with 3 mg/kg THC (daily intraperitoneal injections i.p.).…”
Section: Discussionsupporting
confidence: 93%
“…Further, we showed that impairment of the ghrelin signaling through the knockout of the GHRS does not confer an increased risk of developing THC induced anxiety in adult mice. Our results are consistent with previous reports in rodent models that concluded that prolonged adolescent THC exposure in mice does not have substantive negative impacts on several mPFC-mediated behaviors [47][48][49][50]. In particular, Chen et al [49] treated 28-day-old C57BL6/J mice of both sexes for three weeks with 3 mg/kg THC (daily intraperitoneal injections i.p.).…”
Section: Discussionsupporting
confidence: 93%
“…Specifically, adult rats treated with low doses of THC from PND 30 to 50 spent less time and made less entries in the open arms during the Elevated Plus Maze test [68]. On the other hand, studies reported no long-term differences in THC-exposed males and females [71,72] as well as in C57Bl/6J and DBA/2J male mice [63,65]. In addition, THC has been also found to induce strain-specific anxiolytic effects in Lewis rats, which spent more time in the open arms compared both their vehicle counterpart and THC-exposed Fischer344 rats [73].…”
Section: Risks For Depressive Like-phenotype and Long-term Anxietymentioning
confidence: 95%
“…For example, significant long-term abnormalities in social interaction memory were observed in adolescent rats chronically treated with THC [54,59]. Similarly, short-term and working memory performances were altered when specific tasks (e.g., novel and spatial object recognition, radial arm maze, T maze, Morris water maze) were carried out in both males and females [59][60][61][62][63]. These THC-induced effects on memory have not been reported consistently among studies [64][65][66][67].…”
Section: Risks For Schizophrenia and Cognitive Impairmentsmentioning
confidence: 99%
“…Many demonstrations of impaired working memory have been observed in rodents. For example, male and female mice show deficits in working memory in adulthood following ACE via experimenter-administered injections [ 141 ]. ACE-induced cognitive impairments have also been observed in nonhuman primates.…”
Section: Cannabismentioning
confidence: 99%
“… 28–48 70 -Anxiety -Memory -EPM -Six different object test -No effect -Impaired working memory in females Amygdala, DMS Larger number of DEGs in females Orihuel et al [ 138 ] Rat M, F 3 mg/kg, i.p. 28–48 (every other day) 90 -Reward learning -Pavlovian conditioned approach -Increased goal-tracking -Increased PIT NAc shell Sex-specific changes in transcriptome profile Chen & Mackie [ 141 ] Mouse M, F I.P. injection 10 ml/kg 28–49 65 -Working memory -Anxiety -Delayed alternation T maze -EPM -Impaired working memory -No effect Withey et al [ 142 ] Squirrel Monkey M Intramuscular Injection, 1 mg/kg 27–31 months NS Cognition Discrimination leaning, discrimination reversal Impaired performance Verrico et al [ 143 ] Rhesus Monkey M Intravenous s-a 15–240 μg/kg 28.6–33.6 months 29 months Working memory Delayed match to sample Impaired performance Prini et al [ 155 ] Rat F I.P.…”
mentioning
confidence: 99%